Pengaruh Bantuan Sosial dan Zakat Terhadap Kemiskinan di Sumatera Barat - Putri, Nola; Yeniwati, Yeniwati; Irfan, Muhammad (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2023)
This study describes the extent of the impact the of social assistance, zakat on poverty in West Sumatra using the Human Development Index as a control variable. This study combines cross-sectional data for 17 provinces/cities in West Sumatra with time series his 2011-2020, using Panel Regression methods and Fixed-Effect model selection tests. The results of this study show that (1) social assistance has a positive and insignificant effect on poverty in West Sumatra, and (2) zakat has a positive and insignificant effect on poverty in West Sumatra, (3) the Human Development Index has a negative and significant effect on poverty in Sumatra West.